A Cross sectional study on distribution of ABO and Rh blood group antigens among the blood donors at a tertiary care hospital in Andhra Pradesh, India - Dr. Ponnada Jogi Naidu; Dr. Shamili Moningi (Tropical Journal of Pathology and Microbiology, 2020)
Aims: The study is aimed to determine the distribution pattern of the ABO grouping and Rh typing among blood donors in Great Eastern Medical School and Hospital, Srikakulam and to correlate it with the available data from studies inside India and other parts of the world.Materials and Method: The present study was conducted at Great Eastern Medical School and Hospital, Srikakulam, a tertiary care teaching hospital. All blood donors were done counseling as per NACO guidelines and considered fit for blood donation were included in this study. A total of 5868 blood donors was considered physically screened and declared fit and accepted for blood donation.Results: Out of 5868 donors, 5850 (99.6%) were males and 18 (0.4%) were females. The majority of donors belonged to the age group 26-35 years. The commonest ABO blood group present was B (36.4%) followed by O (35.08%), A (24.4%), and AB (4.12%) while 5743 (97.86%) donors were Rh-positive and 125(2.13%) donors were Rh-negative.Conclusion: Knowledge of the distribution pattern of the different blood groups is very crucial for blood banks and blood transfusion services which significantly contribute to the Health System of the Nation. Knowledge of blood group distribution is important for clinical studies, geographical information, and forensic studies in the general population.